(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of knowledge and practices regarding Dengue fever prevention among residents of Vĩnh Hậu commune, Cà Mau province, in 2025. Đối tượng và phương pháp: Nghiên cứu cắt ngang mô tả từ tháng 8-11 năm 2025 trên 390 người dân tại xã Vĩnh Hậu, tỉnh Cà Mau. Subjects and methods: This descriptive cross-sectional study was conducted from August to November 2025 on 390 residents in Vinh Hau commune, Ca Mau province.Results: 100% of the subjects are knew about Dengue fever, 98.5% knew it is transmitted by mosquitoes, but detailed knowledge about Aedes mosquitoes, biting times, and breeding sites remained limited. Preventive practices were uneven, 51.2% regularly cleaned water containers, 82.3% slept under mosquito nets, other measures were below 25%, and only 2.6% eliminated mosquito larvae. There was a strong association between correct knowledge and correct practice (OR = 3.2; p < 0.001). Conclusion: The people of Vinh Hau commune, Ca Mau province, still have limited in-depth knowledge and practices in disease prevention, especially regarding mosquito larva eradication, which is very low (2.6%). The group with adequate knowledge has a higher ability to practice correctly compared to the group with inadequate knowledge, showing that knowledge plays an important role in changing behavior.